Growth performance, physiological and antioxidant capacity responses to dietary fish meal replacement with insect meals for aquaculture: A case study in red claw crayfish (Cherax quadricarinatus). (10th May 2022) - Wang, Tao; Wang, Xuexi; Shehata, Akram Ismael; Wang, Ruoxuan; Yang, Huiping; Wang, Yilei; Wang, Jianfeng; Zhang, Ziping
Abstract: A 60‐day feeding trial was conducted to evaluate the effects of yellow mealworm (YM) ( Tenebrio molitor ) (9%, 18%, 27% and 36%) and black soldier fly larvae (BSFL) ( Hermetia illucens ) (7%, 14%, 21% and 28%) meal replacing fish meal (FM) on growth performance and antioxidant capacity of red claw crayfish ( Cherax quadricarinatus ). Nine diets, including control, were fed with quadruplicate of 20 crayfish (0.20 ± 0.05 g). The highest weight gain (WG) and lowest feed conversion ratio were observed in crayfish fed YM18 and BSFL14. The highest superoxide dismutase activity and the lowest malondialdehyde content were detected in the hepatopancreas of the crayfish fed YM18 and BSFL14. Compared with the control group, crayfish fed BSFL14 had higher levels of glutathione peroxidase, catalase acid and alkaline phosphatase and the lowest malondialdehyde (MDA) content in hemocytes. The mRNA expression of CqBAF, HSP70 and MnSOD in the hepatopancreas of crayfish showed an increasing trend. Based on the second‐order polynomial regression analysis of WG, the optimal dietary replacement level of FM with YM meal and BSFL was determined to be 21.9% and 17.1% for juvenile C. quadricarinatus .